Ethics management: How to achieve ethical organizations and management? - Snellman, Carita Lilian (Business, Management and Economics Engineering, 2015)
The last decades’ serious organizational scandals that mainly stem from corruption and conflicting interests but also from bribery, favoritism and other wrongdoings have ac-centuated the need for finding instruments for achieving more ethical organizations and management. Ethics management is particularly important in the public sector because public employees and holders of public office are responsible for increasing wellbeing and providing common good for all citizens. Only accountable management striving for integrity through ethical practices and decision making will guarantee ethical organiza-tional behavior. In spite of increasing research on ethics in general and ethics manage-ment in particular, increase in organizational scandals indicates that there is knowledge gap concerning ethical instruments that help to solve ethical problems. The aim of this paper is to shed light on ethical theories and instruments, and wrongdoings in public sec-tor organizations. The main questions are; why is there so much wrongdoing; how can it be reduced; and how can more ethical organization and management be achieved. This is a review paper aiming to provide a review of ethical theories and instruments and dis-cuss serious wrongdoings and the role of ethics in the public sector. The paper contrib-utes to the fields of management and organization, ethics, and public management.